2018
DOI: 10.3390/bioengineering5040093
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Bioconversion of Agro-Industrial Wastes to Industrially Important Enzymes

Abstract: Agro-industrial waste is highly nutritious in nature and facilitates microbial growth. Most agricultural wastes are lignocellulosic in nature; a large fraction of it is composed of carbohydrates. Agricultural residues can thus be used for the production of various value-added products, such as industrially important enzymes. Agro-industrial wastes, such as sugar cane bagasse, corn cob and rice bran, have been widely investigated via different fermentation strategies for the production of enzymes. Solid-state f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
20

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(128 citation statements)
references
References 136 publications
(141 reference statements)
3
105
0
20
Order By: Relevance
“…Till date, especially agricultural waste such as fruit peels, cereal bran, and straw or oil cakes have been successfully used for laccase production. Such residues contain polysaccharides and phenolic compounds that can stimulate both the fungal growth and subsequent laccase production [12]. Our previous study indicated rapeseed oil cake, hay, and sawdust as convenient substrates for laccase production by Myrothecium roridum [13].…”
Section: Introductionmentioning
confidence: 99%
“…Till date, especially agricultural waste such as fruit peels, cereal bran, and straw or oil cakes have been successfully used for laccase production. Such residues contain polysaccharides and phenolic compounds that can stimulate both the fungal growth and subsequent laccase production [12]. Our previous study indicated rapeseed oil cake, hay, and sawdust as convenient substrates for laccase production by Myrothecium roridum [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose is difficult to hydrolyze even after pretreatment as it is closely linked with hemicelluloses and most of its structure is a highly ordered and tightly packed crystal. 31 The addition of xylanases facilitates the access to cellulases and increases the efficiency of cellulose hydrolysis. In addition, systems with xylanase require less cellulase, thus reducing the costs involved in the process of enzymatic hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre esses metabólicos estão as enzimas, que são biomoléculas conhecidas como catalisadores biológicos que encontram aplicações em diversas indústrias, variando desde indústrias de panificação e fabricação de cerveja, celulose para produção de papel, e indústria de detergente. Devido ao seu alto grau de especificidade de substrato e parâmetros operacionais rigorosos e robustos, o uso de enzimas é preferido à catálise química em muitas situações (RAVINDRAN et al, 2018).…”
Section: Enzimasunclassified
“…Resíduos agroindustriais, como bagaço de cana, espiga de milho e farelo de arroz, têm sido amplamente investigados para serem aproveitados como matéria-prima para diferentes estratégias de fermentação com vistas à produção de biomoléculas (RAVINDRAN et al, 2018…”
Section: Introductionunclassified